Holocene Indian Summer Monsoon variations inferred from end-member modeling of sediment grain size in the Andaman Sea. (30th August 2020) - Huang, Yun; Xiao, Jule; Xiang, Rong; Liu, Shengfa; Khokiattiwong, Somkiat; Kornkanitnan, Narumol; Fan, Jiawei; Wen, Ruilin; Zhang, Shengrui; Liu, Jianguo
Abstract: Whether the Indian Summer Monsoon (ISM) Maximum started in the early Holocene or middle Holocene remains a controversial issue. Grain-size measurements were conducted on 157-cm-long core ADM-C1 from the Andaman Sea; the core spanned the last 11.2 kyr BP. Four end-members (EMs) were unmixed using lognormal parametric end-member modeling. Genetic analyses of the grain-size EMs suggested the EM1 and EM2 may correlate with suspension in the upper layers and transportation in the benthic nepheloid layer, respectively, while the EM3 and EM4 were tied with deposition affected by monsoonal currents and sedimentation under extreme events, respectively. The EM3 was dominated by ISM intensity and transported by summer monsoon currents, with increase in the proportion of EM3 reflecting increasing ISM intensity, and vice versa. Variations in EM3 were used to define three stages of ISM evolution, as follows: (1) During 11.2–9.1 kyr BP, EM3 was relatively low, indicating a weak ISM; (2) during 9.1–4.5 kyr BP, EM3 increased substantially, indicating a strengthened ISM; (3) during 4.5-0 kyr BP, EM3 decreased gradually, suggesting a gradual weakening of the ISM. The Holocene ISM Maximum started at ~9.1 kyr BP rather than in the early Holocene, which may have been partly due to the slowdown of the Atlantic meridional overturning circulation (AMOC) during the early Holocene that resulted in a decreased land-sea thermal contrast between the landmass and the Indian Ocean. An additional cause may have been the remnant Northern Hemisphere ice sheets that impeded the northward shift of the Intertropical Convergence Zone (ITCZ). Seven relatively brief decreases in the ISM intensity (events 7, 6, 5, 4, 3, 2, 1) occurred at ca. 10.3, 9.7, 7.3, 5.7, 4.2, 2.4, and 0.8 kyr BP, respectively. They corresponded, within the age uncertainties, to the increased supplies of ice-rafted detritus to North Atlantic sediments, implying that changes in the ISM intensity on millennial scale were dominated by climatic processes in northern high latitudes.